Villa - Muna Sbaihat (My University, 2015)
This project is consisting of residential building (Villa) of two stories, ground floor for the guests of the villa, and the first floor for the residents. Ground floor (293.55m) contains: living room, kitchen, bed room for guests, guest room, bathrooms and gallery. First floor (313.65m) contains: master bedroom with bathroom and dressing room, bedroom for girls with bathroom, bedroom for boys with bathroom, living room, and gallery. In this project the design was depends on purely scientific bases due to all previous years of study. The design was in many aspects: architectural design, structural design, environmental design, mechanical design, electrical design, and safety design. The Villa is in Nablus city at Rafidia Street near of An-Najah national university.

, . (293.55) , , , , . (313.65) , , , , . . : , , , , , . .
Villa